TINGKAT PENDIDIKAN IBU DENGAN KEJADIAN KEP PADA ANAK USIA (3-5 TAHUN) DI POS PAUD TERPADU MULIA SURABAYA - Endang Buda Setyowati (Akademi Kebidanan Griya Husada Surabaya, 2018)
Protein Energy Deficiency (KEP) is a state of malnutrition caused by low consumption of energy and protein in daily food so that it does not meet the nutritional adequacy rate (Ministry of Health, 2000). The incidence of PEM in children aged 3-5 years at the Mulia Integrated Paud Post in Surabaya tends to increase from 2017-2018 by 12.5 - 15%, expected not to exceed the prevalence rate set by MDG's at 15.5%. The purpose of this study was to determine the description of the education level of mothers with the incidence of PEM in children aged (3-5 years) at the Mulia Integrated Paud Post Surabaya in July 2018. Method: the research used was descriptive. The population is 80 children. Sampling using Non Probability sampling with saturated sample techniques, the sample in the study were 80 children. Primary and secondary data collection by weighing children and looking at the mother's level of education from the child's report card. The data is then made a frequency table and cross tabulation and conclusions are then made. Results: From the results of the study it can be concluded that mothers who have a low level of education, the majority of children experience PEM. Therefore, health workers are expected to provide information on balanced nutrition for mothers who have children aged 3-5 years.